2018
DOI: 10.6061/clinics/2018/e656s
|View full text |Cite
|
Sign up to set email alerts
|

Clinical stage and histological type of the most common carcinomas diagnosed in young adults in a reference cancer hospital

Abstract: OBJECTIVES:Cancer in young adults represents a great challenge, both biologically and socially, and understanding the unique characteristics of neoplasms in this age group is important to improving care. We aimed to evaluate the most common carcinomas and their characteristics, such as histological type and clinical stage, in young adults in the largest cancer hospital in Latin America.METHODS:The hospital registry was consulted for the period between 2008 and 2014. Young adults were defined as individuals age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…The most common malignancies are the invasive carcinomas of NST (87.12%) and ductal carcinoma in situ (3.68%), similar to other studies from Africa [ 26 , 27 ], Brazil [ 28 ], and England [ 29 ]. More than half of the cases were of grade 3 and very few were of grade 1, which agrees with a study by Stalk et al [ 30 ] but contrasts with another by Eugenio et al [ 28 ]. High grade tumors have poor prognosis [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The most common malignancies are the invasive carcinomas of NST (87.12%) and ductal carcinoma in situ (3.68%), similar to other studies from Africa [ 26 , 27 ], Brazil [ 28 ], and England [ 29 ]. More than half of the cases were of grade 3 and very few were of grade 1, which agrees with a study by Stalk et al [ 30 ] but contrasts with another by Eugenio et al [ 28 ]. High grade tumors have poor prognosis [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 87%
“…In this study, about half of our cases showed lymphovascular involvement or invasion which primarily indicates poor prognosis [ 28 , 33 ]. The number of affected lymph nodes, which we have no data on, may as well be of prognostic importance.…”
Section: Discussionmentioning
confidence: 99%
“…The present results are in accordance with other authors, who have shown that lung cancer in YA is more commonly detected in women and that adenocarcinoma is more prevalent than in older patients [5,11,14]. In addition, more advanced CS at diagnosis seems to be a trend in young patients [19]. Accordingly, among patients aged 40 years or less, a greater proportion (63.2%, compared with 51.9% of MA and 43.2% of elderly patients, after excluding around 5% of the patients with undetermined CS) in the present series and 57.4% in a surveillance, epidemiology, and end results (SEER) study (compared with 43% of elderly individuals) were diagnosed with disease CS IV [5].…”
Section: Discussionsupporting
confidence: 93%
“…Patients in this age group had no history of alcohol consumption, cigarette smoking, comorbidity, or family history of cancer. Indeed, recent reports have also noted rising cases of CRC among adolescents and young adults (AYAs), [34][35][36][37] and the most commonly involved sites were the distal colon and rectum. 35,38 Unfortunately, the factors influencing this rise are yet to be determined.…”
Section: Dovepressmentioning
confidence: 99%